2006
DOI: 10.1007/s00726-005-0272-z
|View full text |Cite
|
Sign up to set email alerts
|

Brain G protein-dependent signaling pathways in Down syndrome and Alzheimer’s disease

Abstract: Premature aging and neuropathological features of Alzheimer's disease (AD) are commonly observed in Down syndrome (DS). Based on previous findings in a DS mouse model, the function of signaling pathways associated with adenylyl cyclase (AC) and phospholipase C (PLC) was assessed in cerebral cortex and cerebellum of age-matched adults with DS, AD, and controls. Basal production of cAMP was reduced in DS but not in AD cortex, and in both, DS and AD cerebellum. Responses to GTPgammaS, noradrenaline, SKF 38393 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
12
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 33 publications
2
12
1
Order By: Relevance
“…However, when the system was challenged by receptor stimulation of β-adrenoceptor, or using GTPγS, a nonhydrolyzable analog of GTP, or forskolin to directly activate the catalytic subunit of the enzyme, an impaired response was clearly detected in the trisomic mice. Our present results confirm the deficits we reported in the frontal and hippocampal cortices of young adult male Ts65Dn mice [29,30], and in DS individuals [21], where we observed a severe deficiency in AC activity, with a very poor response to various stimulatory signals, including forskolin [21]. In the present work, this reduction was also detected in the hippocampus of Ts65Dn females that could be related to their learning deficits.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…However, when the system was challenged by receptor stimulation of β-adrenoceptor, or using GTPγS, a nonhydrolyzable analog of GTP, or forskolin to directly activate the catalytic subunit of the enzyme, an impaired response was clearly detected in the trisomic mice. Our present results confirm the deficits we reported in the frontal and hippocampal cortices of young adult male Ts65Dn mice [29,30], and in DS individuals [21], where we observed a severe deficiency in AC activity, with a very poor response to various stimulatory signals, including forskolin [21]. In the present work, this reduction was also detected in the hippocampus of Ts65Dn females that could be related to their learning deficits.…”
Section: Discussionsupporting
confidence: 81%
“…Numerous studies have revealed disrupted post-receptor signal transduction, in particular those mediated by G-protein-regulated adenylyl cyclase (AC) [19,20,21,22] and phospholipase C (PLC) [21,22,23,24] in DS brains. Consistent changes found in myoinositol and phospholipid composition of fetal and adult DS brain membranes [25,26,27] may predict deregulation of PLC-linked transduction processes, and our previous studies determined a reduced ability of several brain areas to respond to the indirect (receptor-mediated) and direct stimulation of the PLC [28] and AC [29,30] signaling systems in Ts65Dn mice.…”
Section: Introductionmentioning
confidence: 99%
“…Another study using adult mouse models has suggested a role for two other G protein dependent pathways in DS and Alzheimer disease (34). Our work, however, suggests a wider and more fundamental role for G protein signaling, involving a large number of proteins and appearing as early as the second trimester.…”
Section: Discussionmentioning
confidence: 54%
“…This model replicates many physical and functional abnormalities observed in people with trisomy for chromosome 21. The abnormalities include shorter life expectancies and morphological, neurological, behavioral, structural, and neuronal circuit abnormalities that parallel those in people with DS [8][9][10][11][12][13][14][15]. Furthermore, consistent with the changes demonstrated in imaging and behavioral studies in people with DS [5][6][7], the Ts65Dn model displays deficits in hippocampal structure and function.…”
mentioning
confidence: 83%
“…In spite of significant recent progress in understanding the neurobiology of DS [8][9][10][11][12][13][14][15][16][17], there is as yet little insight into the genes and mechanisms responsible for developmental and age-related changes in cognition and behavior. The 'gene dosage' hypothesis for exploring pathogenesis states that an extra copy of one or more genes, or regulatory elements, on HSA21 is responsible for the changes in brain structure and function -in other words, for all the phenotypes that are characteristic of DS.…”
mentioning
confidence: 99%